(untitled) - Röbbelen, Gerhard (New York, 1989)
Examines such diverse aspects as the chemical nature of vegetable oils, oilseeds as energy crops, the nature and biosynthesis of storage proteins, and the genetics and breeding of oil crops. Also explained are the processing of oilseed crops, the biosynthesis of fatty acids in higher plants, industrial and nonfood uses of vegetable oils, and new annual food crops. Acidic paper. Annotation copyright Book News, Inc. Portland, Or.
Keywords: Cây có dầu,Oilseed plants